Perlindungan Hukum Terhadap Penumpang Angkutan Umum Ditinjau dari Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan - Ida Bagus Ananta Kusuma; I Nyoman Sukandia; I Nyoman Sutama (Fakultas Hukum Universitas Warmadewa, 2024)
For Indonesians, transportation is a very significant activity. It is essential to understand the availability of transportation services that are orderly and entertaining, as well as appropriate to the level of traffic demand. Consequently, a single national transportation system must be created to coordinate road and transit traffic. According to Law No. 22 of 2009 on Road Traffic and Transport and Carrier Liability regarding passenger accidents in public transport on Road Traffic and Transport, the purpose of this review is to outline the various legal protections available to public transport users. By offering safe, convenient, fast, and affordable services, public transport users are afforded legal protection. Public transport must be accessible as it is a crucial daily necessity. The government is in charge of organizing the public transportation system. There are significant issues with legal protection for passengers in the increasing global competition, which requires legal protection.